Mechanical and Antibacterial Properties of Injection Molded Polypropylene/TiO2 Nano-Composites: Effects of Surface Modification - Altan, Mirigul; Yidirim, Huseyin (JOURNAL MATER SCI TECHNOL, 2012)
Polypropylene (PP)/titanium dioxide (TiO2) nano-composites were prepared by melt compounding with a twin screw extruder. Nanoparticles were modified prior to melt mixing with maleic anhydride grafted styrene-ethylene-butylene-styrene (SEBS-g-MA) and silane. The composites were injection molded and mechanical tests were applied to obtain tensile strength, elastic modulus and impact strength. Antibacterial efficiency test was applied on the injection molded composite plaques by viable cell counting technique. The results showed that the composites including SEBS-g-MA and silane coated TiO2 gave better mechanical properties than the composites without SEBS-g-MA. Antibacterial efficiency of the composites varied according to the dispersion and the concentration of the particles and it was observed that composites at low content of TiO2 showed higher antibacterial property due to the better photocatalytic activity of the particles during UV exposure.
Keywords: Nano-TiO2; Polypropylene; Mechanical property; Antibacterial property; Injection molding; TENSILE PROPERTIES; NANOCOMPOSITES; POLYSILOXANES; FRACTURE; Materials Science; Metallurgy & Metallurgical Engineering